2021
DOI: 10.3390/ijms22010457
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of the Radionuclide 131I Using Cationic Fusogenic Liposomes as Nanocarriers

Abstract: Liposomes are highly biocompatible and versatile drug carriers with an increasing number of applications in the field of nuclear medicine and diagnostics. So far, only negatively charged liposomes with intercalated radiometals, e.g., 64Cu, 99mTc, have been reported. However, the process of cellular uptake of liposomes by endocytosis is rather slow. Cellular uptake can be accelerated by recently developed cationic liposomes, which exhibit extraordinarily high membrane fusion ability. The aim of the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In addition, the 2 mol% peptide-modified DOTAP0.250-LP observed showed no morphological changes in the eye tissue sections in its instillation (data not shown), demonstrating the application is safe for the living body when used in an appropriate concentration. Several reports have indicated that neutral liposomes must be modified with ligands or cationic lipids to enhance their interactions with the cell surface [ 45 , 46 , 47 ]. The DOPC/CHO liposomes used in this study had a neutral or weakly negative charge.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the 2 mol% peptide-modified DOTAP0.250-LP observed showed no morphological changes in the eye tissue sections in its instillation (data not shown), demonstrating the application is safe for the living body when used in an appropriate concentration. Several reports have indicated that neutral liposomes must be modified with ligands or cationic lipids to enhance their interactions with the cell surface [ 45 , 46 , 47 ]. The DOPC/CHO liposomes used in this study had a neutral or weakly negative charge.…”
Section: Discussionmentioning
confidence: 99%
“…Recently developed cationic liposomes have accelerated cellular internalization, resulting from a high membrane fusion ability. Cationic liposomes are composed of a classical lipid mixture of neutral lipid 1,2-dioleoyl-sn-glycerol-3-phosphoethanolamine (DOPE) and cationic lipid 1,2-dioleoyl-3-trimethylamine propane (DOTAP), which are used as carrier particles to achieve optimal cargo delivery through the attractive interactions between positively charged liposome surface and negatively charged cargo (such as protein, peptide, or RNA molecules) [ 137 ]. An animal experiment reported that the mRNA encoding a tumor-associated antigen encapsulated by a cationic liposome complex was released at the target site after its intranasal administration in mice, which induced an immune response and prevented tumor growth [ 138 ].…”
Section: Vaccines For Nasal Administrationmentioning
confidence: 99%
“…Owing to its high biocompatibility and non-toxicity, liposomes have been used as nano-drug carriers in tumor treatment [55]. Liang et al labeled a therapeutic radioisotope 131 I onto albumin-encapsulated liposomes to improve vasculature permeability and promote the enrichment of drugs within tumor, so as to enhance the anti-tumor efficacy of radionuclides [56].…”
Section: Organic Nanoparticlesmentioning
confidence: 99%
“…In recent research, Kolašinac et al intercalated radionuclide 131 I into cationic fusogenic liposomes to form the novel nanocomposites. Compared with free iodine uptake, the usage of nanocomposites achieves a 10% increase in drug delivery efficiency with its special membrane fusion ability [55].…”
Section: Organic Nanoparticlesmentioning
confidence: 99%